The Inspection of the rural-urban educational gap in Spain - Santamaria Luna, Rogeli (Avances en Supervisión Educativa, 2018)
Some data on education in rural areas of Spain are analyzed. The data come from different sources: external evaluations to consider the rural habitat (diagnostics, TIMSS-PIRLS, PISA), data on educational level, permanent training or early school leaving (INE, Eurostat). The persistence of the rural-urban gap still exists, which is why governments are suggested specific objectives for the improvement of the rural school within the framework of a Rural Education Plan. The teacher survey shows the perception of little continuous training in rural school, especially among teachers with less than 18 years of teaching experience. It also confirms that they have little training in fundamental issues in this environment: organization and methodology in multigrade classrooms, environmental knowledge, environmental education and rural development, key factors to achieve a school rooted and involved with the rural environment. At this point, the necessity of the Zone Inspection is stressed, which, in schools with excessive teaching mobility, is the one that can disseminate good practices and give certain coherence and continuity to the actions of the team of teachers when none of the teachers who applied them. At the same time, the Zone Inspection can help assess, with the Senate and the Educational Community, the educational service that is offered and can provide the Administration with an accurate view of the situation in the rural world. In the author’s opinion, it is important that the inspectors and education inspectors know the context of the rural world, its problems and strengths and put this knowledge at the service of rural educational and socio-community improvement.